In vitro Biological Evaluation of 1,2,4-triazole Mannich Base - Mahmood Sherzad Rafaat; Arzu Karatepe; Serhat Keser; Şule İnci; Semih Dalkılıc (BioMed Target Journal)
Biological evaluation of a 1,2,4-triazole mannich base that has been synthesized for interesting behavior in medicinal chemistry, so it’s interesting to synthesize triazole derivatives and investigate their biological properties to evaluate their capacity in medicine. The aim of this study evaluate the antimicrobial, anticancer, and antioxidant activities of a 1,2,4-triazole Mannich base derivative and its power in the treatment of diseases. For antimicrobial activity four bacterial strains and one fungal strain based on the agar disc diffusion. While used two cancer cell lines for anticancer activity which are known as Hep-G2 and MCF-7; the antioxidant activity of the compound used three different radical species include OH•, ABTS•+, and DPPH•, and also determine the antioxidant activity of the compound after extracting vitamins A, C, E, and MDA in the S. cerevisiae yeast cell by HPLC. The results of this study show the positive role of a derivative 1,2,4-triazole mannich base as antimicrobial and antiradical assays, particularly when treated with C. albicans and OH• radical that significantly reduced growth of the fungal and the radical compared to others. In addition, it didn’t exhibit any cytotoxicity to reduce both cancer cell lines. In conclusion, the compound's ability is different from one assay to another, increasing its concentration efficiency affects the radical scavenging, and inhibits microorganism growth.